THE TECHNOLOGY OF INFORMATION PROCESSING BY HIGHER EDUCATIONAL INSTITUTION STUDENTS: STAGES, METHODS, TECHNIQUES - Denis V. Tatyanushkin (Высшее образование в России)
The article presents the classification of information types on different criteria. The requirements for the quality of scientific information are characterized. The author considers the nature of modern students’ interaction with the digital information environment and demonstrates the need for development of students’ information processing skills. The technology of information processing by students is introduced. The paper describes the basic methods and techniques of working with the texts contents when fulfilling creative tasks and writing scientific research papers. The results of this research have practical application ineducational process of higher educational institution.